LITERASI DIGITAL SEBAGAI INSTRUMEN MEMAHAMI SISWA DAN PENGENALAN KOMPETENSI GURU SLB - Nur, Muhammad Khaerul; Aisyah, Aisyah; Marsus, Ismat; Hamson, Zulkarnain (Yayasan Education and Social Center, 2025)
In the digital era, technology plays an important role in supporting inclusive education, especially in Special Schools (SLB). Teachers need to have digital literacy competencies in order to understand the characteristics of students with special needs and develop appropriate learning methods. This training aims to equip SLB teachers with digital literacy skills as an instrument in understanding students and improving their professional competence in using educational technology. This training is carried out in one day (7 hours) using workshop and direct practice methods. The material provided includes an introduction to digital literacy in the context of special education, the use of technology to understand students, the development of digital-based learning media, and digital learning evaluation strategies. Through interactive sessions and simulations, participants are given the opportunity to apply various platforms and applications to create a more inclusive and innovative learning environment. The results of this training are expected to improve teachers' digital competence, enabling them to design and implement technology-based learning strategies effectively. In this way, education for students with special needs can be more adaptive, interactive, and in accordance with their individual needs. This training also encourages teachers to continue developing their digital skills in order to create higher quality learning in SLB